Exhaustive Extraction of Bioactive Components from Sargassum cristaefolium Brown Seaweed: Antioxidant Potential and Bioactivity - Rohim, Abd.; Khurniyati, Maylina Ilhami; Sutama, Daning Kinanti; Rahmadina, Safira; Putri, Nabilla Dwi (HAYATI Journal of Biosciences, 2025)
Bioactive components are essential ingredients of functional foods, supplements, pharmaceuticals, etc. Sargassum cristaefolium brown seaweed, as an Indonesian marine resource, provides promising bioactive components. The present study was to extract the total bioactive components of S. cristaefolium with a microwave instrument. The extraction method was done serially using different polarity solvents (1st-stage: non-polar, 2nd-stage: semi-polar, Final-stage: polar). Yielded extracts were analyzed for bioactive compounds, functional groups, total phenolic and flavonoid, and antioxidative activities. The results showed that all staged extractions obtained bioactive compounds with various characteristics. However, the 2nd-stage extract was superior, and it exhibited the highest total phenolic and flavonoid (17.53±0.78 mg GAE/g, 72.64±3.01 mg QE/g), the richest volatile bioactive compounds (neophytadiene and phytol were dominant), and the predominant bioactive compound of antioxidative (oleoylethanolamide). Their functional groups confirmed the structure of antioxidative phenolic molecules: C―C stretching skeleton (phenyl/aromatic core), C―H stretching, C―H bending, and O―H stretching. The strongest primary (1439.84±63.02 µg/ml) and secondary (389.73±16.71 µg/ml) antioxidant activities were presented by the 2nd-stage extract. The efficiency of MAE and the potential of S. cristaefolium were promising for developing functional foods and pharmaceuticals that relate to antioxidants in the future.